2004
DOI: 10.1007/s11745-004-1327-y
|View full text |Cite
|
Sign up to set email alerts
|

Separation of vitamin E (tocopherol, tocotrienol, and tocomonoenol) in palm oil

Abstract: Previous reports showed that vitamin E in palm oil consists of various isomers of tocopherols and tocotrienols [alpha-tocopherol (alpha-T), alpha-tocotrienol, gamma-tocopherol, gamma-tocotrienol, and delta-tocotrienol), and this is normally analyzed using silica column HPLC with fluorescence detection. In this study, an HPLC-fluorescence method using a C30 silica stationary phase was developed to separate and analyze the vitamin E isomers present in palm oil. In addition, an alpha-tocomonoenol (alpha-T1) isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 11 publications
5
100
0
Order By: Relevance
“…The bioactive compounds of USF are vitamin E of 0.80%, phytosterols of 9.16%, squalene of 1.14% [6]. The difference of PFAD as vitamin E containing material form other vitamin E sources is rich in tocotrienols [10,11]. Lewis (2001) indicated that tocotrienols have hypocholesterolaemic property and have the ability to reduce LDL cholesterol level [12].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds of USF are vitamin E of 0.80%, phytosterols of 9.16%, squalene of 1.14% [6]. The difference of PFAD as vitamin E containing material form other vitamin E sources is rich in tocotrienols [10,11]. Lewis (2001) indicated that tocotrienols have hypocholesterolaemic property and have the ability to reduce LDL cholesterol level [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the separation of mixed tocopherol homologues has been very challenging because of their high structural similarity. The available methods for this problem mainly include various chromatographic technologies, such as high performance liquid chromatography (Ng et al, 2004;Pyka & Sliwoik, 2001), capillary electrochromatography (Chaisuwan et al, 2008), microemulsion electrokinetic chromatography (Chang et al, 2006), nano-liquid chromatography (Fanali et al, 2002), supercritical fluid chromatography (Jiang et al, 2003) and low pressure column chromatography (Wan et al, 2008). Although these technologies could give effective separation for the tocopherol homologues, they are almost only applied at a laboratory scale on account of the low throughput capacity and large consumption of absorbents and solvents or the requirement for special equipment.…”
Section: Separation Of Structurally Related Natural Compoundsmentioning
confidence: 99%
“…Tocopherols differ from tocotrienols in that there are three double bonds in the side chain of the tocotrienols. There is a possibility that vitamin E isomers with only one or two double bonds in the side chain are present in palm oil (Ng et al, 2004). Tocopherol and tocotrienol have different biological activities towards free radicals and may play significant role as signaling molecule in cellular activities (Sue-Mian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%